重型汽车变速器的齿轮-轴系统动力学仿真建模 - 刘文耀; 范进桢; 秦贵林; 吴昭同 (Jixie chuandong)
The gear-axial system is the main component of heavy vehicle transmission.The transmission gear ratio and power transmit route are changed along with its shifting position.In the transmission,15 shifting are three fixed axles drive,and reverse 12 shifting are four fixed axles drive.The dynamics modeling and Matlab/Simulink moulds are built for 1 shifting and reverse 1 shifting of transmission.A method of modeling and simulation for the research of heavy vehicle transmission is offered.